2014
DOI: 10.1111/j.1755-3768.2014.t001.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between ocular optical components and refractive errors in bank’s Employees of Sari, Iran

Abstract: Purpose To investigate the association between ocular optical components and refractive errors in bank’s employees of Sari, Iran Methods In this cross sectional study 398 bank’s employees of Sari, Iran were selected, 232 of them used the eyes for close work (computers, etc…) for a minimum of 7 hours per day for the 5 past years. The other 166 bank’s employees acted as a control group and did not did a close work more than one hour daily for the 5 past years. Age of the participants were between 25 to 40 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, as refractive errors are caused by a mismatch between these parameters, different correlations are found in each refractive group 5 . In particular, the influence of variations in axial length on refractive error has been clearly established, 6–8 but the importance of differences in corneal power, for example, is less clear, with some studies confirming 9–11 and others 12,13 not showing a significant influence. Similarly, while some reports have shown that the anterior chamber depth ( ACD ) is generally deeper in myopes than in hypermetropes, 10,11,14 other authors were unable to confirm this finding 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, as refractive errors are caused by a mismatch between these parameters, different correlations are found in each refractive group 5 . In particular, the influence of variations in axial length on refractive error has been clearly established, 6–8 but the importance of differences in corneal power, for example, is less clear, with some studies confirming 9–11 and others 12,13 not showing a significant influence. Similarly, while some reports have shown that the anterior chamber depth ( ACD ) is generally deeper in myopes than in hypermetropes, 10,11,14 other authors were unable to confirm this finding 15,16 .…”
Section: Introductionmentioning
confidence: 99%